VTE: Treatment, Prevention of Recurrence, Thrombolysis - Nichols, Emma Hitt (MD Conference Express, 2014)
Venous thromboembolism (VTE) is a common problem, at a prevalence of 1 to 2 VTEs per 1000 patients, with an in-hospital fatality rate of up to 12%. This article discusses novel oral anticoagulants that have become available for treatment over the past 5 years, the prevention of recurrent VTE, and thrombolytic therapy for the treatment of acute pulmonary embolism.